Морфологічні та функціональні особливості пилку представників Amelanchier Medik. в НДП «Софіївка» НАН України - Андрієнко, О.Д.; Опалко, А.І.; Опалко, О.А.; Сорокіна, С.І. (Фактори експериментальної еволюції організмів, 2015)
Aims. Awareness of the importance of the representatives of the genus Amelanchier Medik. concerning perspectives of enriching genetic resources, in particular to rare valuable fruiting races and importance of the information relating to pollen quality for botanical, genetic and breeding purposes prompted the study of morphological and functional pollen grains features of some alien Amelanchier spp. Methods. The pollen quality was determined by acetocarmine pollen viability test, morphological characteristics were evaluated visually and by means of measurements. Results. It was clarified that the studied species have pollen grains different in shape, size and fertility. However, the viability of pollen species A. florida and A. asiatica is higher, compared to A. utahensis. Conclusions. Species with high pollen viability can be considered as better adapted, and the adaptability level of A. utahensis require more in-depth study according to other criteria. Keywords: acetocarmine pollen viability test, plant collections, genus-area, pollen grains, taxonomy genus Amelanchier.